Integration of miRNA and mRNA expression profiles reveals microRNA-regulated networks during muscle wasting in cardiac cachexia - Moraes, Leonardo N. [UNESP]; Fernandez, Geysson J. [UNESP]; Vechetti-Júnior, Ivan J. [UNESP]; Freire, Paula P. [UNESP]; Souza, Rodrigo W. A. [UNESP]; Villacis, Rolando A. R.; Rogatto, Silvia R.; Reis, Patricia P. [UNESP]; Dal-Pai-Silva, Maeli [UNESP]; Carvalho, Robson F. [UNESP] (Springer Nature, 2017)
Cardiac cachexia (CC) is a common complication of heart failure (HF) associated with muscle wasting and poor patient prognosis. Although different mechanisms have been proposed to explain muscle wasting during CC, its pathogenesis is still not understood. Here, we described an integrative analysis between miRNA and mRNA expression profiles of muscle wasting during CC. Global gene expression profiling identified 1,281 genes and 19 miRNAs differentially expressed in muscle wasting during CC. Several of these deregulated genes are known or putative targets of the altered miRNAs, including miR-29a-3p, miR-29b-3p, miR-210-5p, miR-214, and miR-489. Gene ontology analysis on integrative mRNA/miRNA expression profiling data revealed miRNA interactions affecting genes that regulate extra-cellular matrix (ECM) organization, proteasome protein degradation, citric acid cycle and respiratory electron transport. We further identified 11 miRNAs, including miR-29a-3p and miR-29b-3p, which target 21 transcripts encoding the collagen proteins related to ECM organization. Integrative miRNA and mRNA global expression data allowed us to identify miRNA target genes involved in skeletal muscle wasting in CC. Our functional experiments in C2C12 cells confirmed that miR-29b down-regulates collagen genes and contributes to muscle cell atrophy. Collectively, our results suggest that key ECM-associated miRNAs and their target genes may contribute to CC in HF.